APPOINTMENT OF DATO’ REDZA RAFIQ AS LGU MEMBER STRENGTHENS USM-INDUSTRY COLLABORATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 26 June 2015 – Education Minister II Dato’ Seri Idris Jusoh has appointed the Chief Executive of the Northern Corridor Implementation Authority (NCIA) Dato' Redza Rafiq Abdul Razak, 47, as a member of the USM Board of Governors effective 1 June 2015 for the duration of three years.